Melioidosis in Pahang: a review from registry data 2011-2015 - How, Soon Hin; Zainulabid, Ummu Afeera; Mahmud, Fatihah; Mohd Ibrahim, Mohamad Shafiq; Lim, Bee Chiu; Bhajan Singh, Kiren Kaur; Loh, Thian Chee; Fong, Voon Ken; Sulong, Mohd Rahim (2021)
Reviews of melioidosis cases were conducted throughout the state of Pahang, Malaysia, from 2000 to 2003 and 2005 to 2006, found that there were high annual incidences (6.0 to 6.1 per 100 000 population) and mortality rates (44% to 54%) among adult melioidosis patients compared to other endemic areas where mortalities were between 19 to 39%. Of the remaining surviving patients, only 51.9% received suitable antibiotics for at least two weeks, and eradication therapy was not provided to most patients as per reported in 2000-2003 data. The clinical manifestation of melioidosis in Pahang varied somewhat in comparison with the other endemic countries. In Australia and Thailand, the incidences of localized melioidosis were reported at 54% and 40%, respectively, but only 8% was reported in Pahang. A series of programs on medical education has since been introduced throughout Pahang, and a registry has been created to track the effects.